Pengembangan Model Pembelajaran ADaBta untuk Meningkatkan Keterampilan Literasi Dasar dan Karakter Bertanggung Jawab Siswa pada Madrasah Ibtidaiyah di Kabupaten Lombok Timur - Muslihan Muslihan; Lalu Awaludin Akbar (CV. Creative Tugu Pena, 2026)
This study aims to develop the Observe, Listen, Read, and Tell (ADaBta) learning model to enhance basic literacy and the character of responsibility among Madrasah Ibtidaiyah students. Using the Research and Development (R&D) method with the ADDIE model—Analyze, Design, Develop, Implement, and Evaluate—this study systematically designed and tested the model. Validity was assessed by five experts through CVR and CVI analyses, while practicality was examined via teacher and student questionnaires. Effectiveness was analyzed using MANOVA. The findings reveal that the ADaBta model is highly valid, with average CVR and CVI values of 1.00, and highly practical, with teacher responses averaging 91.59% and student responses 91.39%. The model also proved effective in improving basic literacy (ES = 1.087), responsibility character (ES = 1.813), and both aspects simultaneously (ES = 0.947). The ADaBta model aligns with the needs of Madrasah Ibtidaiyah students by integrating local folklore and national heroes from Lombok, combined with activity-based multisensory learning. Theoretically, this research contributes to the development of activity-based learning approaches, demonstrating that multisensory and culturally contextual strategies can enhance both literacy and character values simultaneously. Practically, the ADaBta model serves as a structured guide for teachers to implement engaging, relevant, and efficient learning processes at elementary levels. Socially, the model supports national literacy and character education movements by fostering competent, responsible learners and promoting contextual, meaningful education for Indonesian students